2009
DOI: 10.1063/1.3129707
|View full text |Cite
|
Sign up to set email alerts
|

Role of phonon in the thermal and electrical transports in metallic nanofilms

Abstract: Thermal rectification and phonon scattering in silicon nanofilm with cone cavity J. Appl. Phys. 112, 054312 (2012); 10.1063/1.4749394Contributions of electron and phonon transport to the thermal conductivity of GdFeCo and TbFeCo amorphous rare-earth transition-metal alloysThe electronic thermal transport in metallic nanofilms has been extensively studied. There are, however, rare reports on the influence of phonon on the thermal and electrical transports in metallic films. In the present work, equilibrium mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…For example, in the case of bulk cu at room temperature, the MD result in Ref. [77] of k ph = 18 W/mK is much smaller than the experimental thermal conductivity k exp = 401 W/mK, again highlighting the dominant role played by electrons in thermal transport.…”
Section: Phonon Contribution and Molecular Dynamicsmentioning
confidence: 83%
See 2 more Smart Citations
“…For example, in the case of bulk cu at room temperature, the MD result in Ref. [77] of k ph = 18 W/mK is much smaller than the experimental thermal conductivity k exp = 401 W/mK, again highlighting the dominant role played by electrons in thermal transport.…”
Section: Phonon Contribution and Molecular Dynamicsmentioning
confidence: 83%
“…For example, in Ref. [77] it was found that differences in the group velocity and also surface scattering reduced the value of k ph . Films with thickness in the range 10-30 nm were found to have k ph ~ 5-6 W/mK [77].…”
Section: Phonon Contribution and Molecular Dynamicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Chantrenne et al [28] investigated the electron and phonon contributions on the thermal conductivity of aluminum films with a thickness range from 2 to 20 nm and found that it remarkably dropped below the bulk value. Feng et al [29] studied the in-plane thermal conductivity of nanoscale copper films and concluded that even though the lattice contribution in metallic films is enhanced compared to that in bulk metal, it is still relatively small compared to that of electrons.…”
Section: Introductionmentioning
confidence: 98%
“…At the nano scale, the thermal transport decreases due to boundary scattering of electrons and phonons, and size effects (Yuan and Jiang 2006). Since the mean free path for electrons is larger than that of phonons, electrons suffer more scattering than phonons and therefore their contribution to thermal transport decreases (Feng et al 2009). Even then the contribution of conducting electrons is crucial in thermal transport.…”
Section: Effect Of Temperature Controlmentioning
confidence: 99%